2013
DOI: 10.1371/journal.pone.0071868
|View full text |Cite|
|
Sign up to set email alerts
|

Diabetes-Induced Superoxide Anion and Breakdown of the Blood-Retinal Barrier: Role of the VEGF/uPAR Pathway

Abstract: Diabetes-induced breakdown of the blood-retinal barrier (BRB) has been linked to hyperglycemia-induced expression of vascular endothelial growth factor (VEGF) and is likely mediated by an increase in oxidative stress. We have shown that VEGF increases permeability of retinal endothelial cells (REC) by inducing expression of urokinase plasminogen activator receptor (uPAR). The purpose of this study was to define the role of superoxide anion in VEGF/uPAR expression and BRB breakdown in diabetes. Studies were per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 44 publications
2
26
0
Order By: Relevance
“…In addition, our findings are also supported by previous studies performed in brain [24,41] and retinal ECs [42]. Notably, our results have shown significant differences in endothelial response to hypo or hyperglycemic conditions which manifested through differential release of VEGF when ECs were cultured with or without abluminal astrocytes (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, our findings are also supported by previous studies performed in brain [24,41] and retinal ECs [42]. Notably, our results have shown significant differences in endothelial response to hypo or hyperglycemic conditions which manifested through differential release of VEGF when ECs were cultured with or without abluminal astrocytes (Figure 3).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, activation of the uPA/uPAR pathway also contributes to increased retinal vascular permeability in diabetic rats through proteolytic disruption of VE-cadherin. 38 El-Remessy et al 37 have also reported increased matrix metalloproteinase MMP-9 activity downstream of uPA/uPAR signaling in diabetic mice retina which leads to ECM disruption in retinal vessels. Absence of uPAR in uPAR À/À mice results in blockade of diabetes-induced increase in retinal vascular permeability and MMP-9 activity.…”
Section: Retinal Hemorrhage and Inflammationmentioning
confidence: 95%
“…10,35 Urokinase plasminogen activator (uPA), a component of the fibrinolytic system, is increased in epiretinal membranes obtain from patients with PDR 36 and retinal uPA receptor (uPAR) expression is increased in diabetic rats. 37 Upon activation, uPA converts plasminogen to plasmin, which mediates fibrinolysis and can activate matrix metalloproteinases. In addition, activation of the uPA/uPAR pathway also contributes to increased retinal vascular permeability in diabetic rats through proteolytic disruption of VE-cadherin.…”
Section: Retinal Hemorrhage and Inflammationmentioning
confidence: 99%
“…In this context, rod-derived cone viability factor injected into the eye of the P23H transgenic rat model of RP preserved the vision by increasing cone survival and function (Yang et al, 2009). Clinical trials with encapsulated ARPE-19 cells secreting CNTF into the vitreous of patients with RP and AMD showed evidence of photoreceptor protection and/or improved visual acuity (Birch et al, 2013;Emerich and Thanos, 2008;Sieving et al, 2006;Talcott et al, 2011;Zhang et al, 2011).…”
Section: Efficacy Of Neurotrophic Factorsmentioning
confidence: 99%